Pengaruh Lingkungan Kerja Fisik, Kompensasi dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan pada Karyawan AMP (Asphalt Mixing Plant) PT Aneka Bangun Sarana (ABS) Gombong - Naufal Fadli Wibowo; Anton Prasetyo (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2022)
Purpose of this study was to determine the effect of the Physical Work Environment, Compensation and Work Motivation on the Work Productivity of Employees of PT Aneka Bangun Sarana (ABS) Gombong. The data used in this study is primary data. This study used 37 respondents as research samples drawn based on saturated sampling. The method of data analysis used multiple linear regression analysis with the help of SPSS 26 for windows. The results of the study based on the t test showed that the Physical Work Environment variable had a significant effect on the Work Productivity of PT Aneka Bangun Sarana (ABS) Gombong employees, the Compensation variable had a significant effect on the Work Productivity of PT Aneka Bangun Sarana (ABS) Gombong employees, the Work Motivation variable had a significant effect on Work Productivity of PT Aneka Bangun Sarana (ABS) Gombong. The variables of the Physical Work Environment, Compensation, and Work Motivation together have a significant effect on the Work Productivity of the Employees of PT Aneka Bangun Sarana (ABS) Gombong. The results of testing the coefficient of determination of the R Square value of the Employee Productivity variable are influenced by the Physical Work Environment, Compensation and Work Motivation of 62.8% and the remaining 37.2% of the Employee Productivity variable is influenced by variables outside this research model.